Students’ Perception on Learning Writing Skill through Edmodo Media - Sulis Wahyuningtyas; Dihliza Basya; Dyah Ayu Nugraheni (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2017)
This study aims to investigate student’s perception in writing skill through Edmodo Media at Second Grade of SMK Kesehatan TPA Jember. This research was categorized as mixed method.The design of this research was convergent parallel design; the purpose of a convergent mixed methods design is to collect both quantitative and qualitative data. The research subjects in this research are second grade students which are consist of 66 students as population, 33 students are chosen to be a sample, but the researcher chooses 3 students that representative from any kind of students to make the research efficiently. The data of the study were in the forms of qualitative and quantitative data. The qualitative data were obtained by interview, observation and documentation. Meanwhile, the quantitative data were acquired conducting through questionaries. The result of questionaries showed the students’ perception on writing skill through Edmodo have 75,1% students agree in Edmodo, it means that students have positive perception in learning writing through Edmodo.